Evaluation of the effectiveness of a phase three specialised heart failure cardiac rehabilitation programme on cardiovascular risk factor profile. (2nd August 2021) - Fallon, Noeleen; Quirke, Mary; Edgeworth, Caroline; O'Mahony, Rose; Flynn, Nora; McGeary, Patricia; Maher, Vincent; Jones, Victoria; McKee, Gabrielle
Abstract : Background/Aims: Cardiac rehabilitation has long been seen as effective for many cardiovascular diseases and, more recently, as having a positive impact on patients with heart failure. To evaluative the effectiveness of a phase three specialised heart failure cardiac rehabilitation programme on patients' cardiovascular risk factor profile. Methods: This retrospective, longitudinal study examined profile factors of patients, pre- and post-cardiac rehabilitation programme. Patients with New York Heart Association class I–III, of any origin, were recruited through a specialised heart failure service to a 10-week exercise and education programme. Outcome variables included anxiety, depression, quality of life (Minnesota), 6-minute walking test result, blood pressure, weight, waist circumference, body mass index, Duke Activity Status Index and self-care, and were analysed with the Statistical Package for the Social Sciences using repeated measures t-test. Results: 100 patients were eligible and 85 patients completed the programmes. Mean age was 66 years, 80% male, 59% were New York Heart Association class I and 73% had ejection fraction of ≤40%. There was a significant improvement in 6-minute walking test, systolic blood pressure, quality of life and anxiety post programme. Conclusions: In-hospital and out of hospital cardiac care has developed significantly, especially in acute symptom control. More recently, emphasis has been put on the long-term control of other risk factors. This study contributes to the literature indicating that attendance at a hospital-based phase three cardiac rehabilitation programme providing supervised, tailored exercise, with intensive education and psychological support, is effective in reducing risk factors and improving quality of life in patients with lower grades of heart failure.